Risk of conversion to bipolar disorder in patients with late-onset major depression. (22nd July 2022) - Elefante, Camilla; Brancati, Giulio Emilio; Petrucci, Alessandra; Gemmellaro, Teresa; Toni, Cristina; Lattanzi, Lorenzo; Perugi, Giulio
Abstract : To evaluate the impact of age at onset on late-life depression course and on risk of conversion to bipolar disorder (BD). A retrospective chart review of 100 elderly patients (age ≥ 65 years) diagnosed with a moderate-to-severe depressive episode and followed up for at least 18 months was conducted. Among patients affected by major depressive disorder ( N = 57), follow-up morbidity differences between those with typical onset depression (TOD) (<60 years) and those with late-onset depression (LOD) (≥60 years) were investigated using Wilcoxon rank-sum test and Cox proportional hazard model. Patients belonging to the LOD group had a significantly lower percentage of follow-up time spent with depressive symptoms compared with patients with TOD ( r = 0.36; P = 0.006), but significantly more time spent with (hypo)manic episodes ( r = −0.31; P = 0.021). Moreover, LOD was significantly associated with a faster conversion to BD (hazard ratio = 3.05; P = 0.037). Depression first emerging in late life may represent an unstable condition with a high risk to convert to BD. Given the potential clinical implications, further studies on the course of LOD are required.